Technical-Economic Assessment of an LPG Pipeline: An Analytical Approach to Strengthening Energy Security in Perú - Contreras Panibra, Abelardo; Sinchitullo Gómez, Joseph Jean; Castillejo Mendez, Ronaldo Robinson; Condori Inga, Yanet Gloria (LACCEI, 2025)
This study evaluates the technical and economic feasibility of a pipeline for LPG transportation between Pisco and Ventanilla, Peru. In the context of increasing dependence on LPG imports, the decline in domestic production of natural gas liquids, and logistical disruptions caused by anomalous ocean waves, the pipeline emerges as a strategic solution to strengthen the country’s energy security. The analysis considers investment (CAPEX) and operational (OPEX) costs under different scenarios, aligned with local and international regulations. The results show that, although the pipeline’s total average cost exceeds that of maritime transport, its implementation mitigates critical vulnerabilities in the supply chain, ensuring continuity. The sensitivity analysis highlights optimization opportunities that could reduce costs by up to 2.6 USD/Bbl, improving the project’s competitiveness. Beyond its practical applicability, this research provides a valuable theoretical foundation for future pipeline projects related to energy security. This study proposes strategies to ensure the pipeline’s feasibility, including the incorporation of state financial mechanisms and the development of partial segments to serve strategic areas in key energy nodes.